Sargassum spp. accumulation and transport by mesoscale eddies - R. Sosa-Gutierrez; R. Sosa-Gutierrez; J. Jouanno; L. Berline (Ocean Science, 2025)
The proliferation of pelagic Sargassum spp. (Sargassum) in the tropical Atlantic has significant ecological and socioeconomic impacts. While large-scale ocean circulation patterns influence the basin-scale distribution of Sargassum, the role of mesoscale eddies in their local accumulation and transport has not been quantitatively assessed so far. This study investigates the relationship between mesoscale eddies and Sargassum dynamics using satellite observations. By analyzing 13 years of remote sensing observations, we demonstrate that both cyclonic and anticyclonic long-lived mesoscale eddies can trap and transport Sargassum. However, results show that, in cyclonic eddies, Sargassum cover is higher and tends to accumulate during its lifetime, while within anticyclonic eddies the Sargassum cover is usually weaker and tends to decrease. These findings align with recent studies highlighting the role of eddies in shaping the distribution of floating debris and provide an important observational basis for the development of Sargassum drift models.